Philanthropy Movement for Socially-Sustainable Community Development: Evidence from the Tribal Local of Talang Mamak, Riau Province, Indonesia - Muhammad Irham (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2020)
This research reveals Islamic philanthropy through a sustainable community development program initiated by Amil Zakat Agency (Lembaga Amil Zakat), Dompet Dhuafa, Riau Province. The research traces the Da’i Cordofa program, which is a social movement for empowerment people in outback Riau, Indonesia. The study is field research that used the qualitative method. It collected data by observation, documentation, and interview process. Resulting show that is implementing the Da’i Cordofa program has influenced local people, where they are adaptable to increase religiosity. Meanwhile, the philanthropy program has been implemented by accompanying, guiding, and empowering local people to create a new habit for prosperity. The funding of philanthropy collects from donator for creating a new community development program that is developed to socially-sustainable local people in Talang Mamak local occasion, Riau.